2021
DOI: 10.3390/ijms22010459
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Urine Stem Cell-Derived Extracellular Vesicles Reveals B Cell Stimulating Cargo

Abstract: Elucidation of the biological functions of extracellular vesicles (EVs) and their potential roles in physiological and pathological processes is an expanding field of research. In this study, we characterized USC–derived EVs and studied their capacity to modulate the human immune response in vitro. We found that the USC–derived EVs are a heterogeneous population, ranging in size from that of micro–vesicles (150 nm–1 μm) down to that of exosomes (60–150 nm). Regarding their immunomodulatory functions, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 112 publications
1
12
1
Order By: Relevance
“…Through flow cytometry analysis, we found that the isolated USCs expressed some traditional MSC-surface markers, such as CD44 and CD90. However, unlike the previous studies, 26 , 51 the isolated USCs were weakly positively for CD73 and CD105. The difference in immunophenotype between different USCs may be attributed to the cell heterogeneity of USCs.…”
Section: Discussioncontrasting
confidence: 99%
“…Through flow cytometry analysis, we found that the isolated USCs expressed some traditional MSC-surface markers, such as CD44 and CD90. However, unlike the previous studies, 26 , 51 the isolated USCs were weakly positively for CD73 and CD105. The difference in immunophenotype between different USCs may be attributed to the cell heterogeneity of USCs.…”
Section: Discussioncontrasting
confidence: 99%
“… 45 In addition, EVs from human urine MSCs (U-MSCs) reduce T-cell proliferation in response to anti-CD3/CD28 stimulation. 46 EVs can also increase the apoptosis of T cells, as reported for mouse BM-MSC EVs. 47 Besides, BM-MSC EVs inhibit the activation of mouse splenocytes mediated by Toll-like receptor 4 (TLR4) and T-cell receptor leading to the inhibition of nuclear factor κ-light-­chain-enhancer of activated B cells (NF-κB) and nuclear factor of activated T cells 1.…”
Section: Immunomodulatory Effects Of Msc Evssupporting
confidence: 65%
“…Similarly, a recent study carried out by Cao et al also revealed that alveolar bone-derived stem cells secreted mainly IL-6 and MCP-1, and thus, at least partially, explained mechanisms behind their immunosuppressive capacity [37]. Intriguingly, IL-6 was also de-scribed as a part of extracellular vesicles derived from the UDSCs [29]. Moreover, these vesicles carried multiple bioactive molecules which could stimulate B-Lymphocytes and simultaneously suppress the function of T-Lymphocytes.…”
Section: Discussionmentioning
confidence: 81%
“…Paradoxically, UDSCs secretome has not been sufficiently characterized. Several studies described immunomodulatory effect of exosomes derived of UDSCs [29][30][31]. Here, we performed the analysis of the secretion of the basic cytokines and chemokines under standard in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation